Creative wriiting : for senior high school and beyond - Rolando A. Bernales (Malabon City : Mutya Publishing House, Inc., 2022)
"This book is divided into three parts called Itineraries equivalent to units. Each itinerary consists of two or three sub-parts called Destinations equivalent to chapters. Each itinerary opens with in this itinerary a list of learning competencies that are expected to be developed among students. These competencies are culled from the subjects curriculum guide provided by Department of Educations."
Keywords: Creative writing